Age and growth of Aplodinotus grunniens (Perciform: Sciaenidae) in the mid-Usumacinta River - Hernández-Gómez, Raúl Enrique; Contreras -Sánchez, Wilfrido Miguel; Perera-García, Martha Alicia; Cuenca-Soria, Carlos Alberto; Valenzuela-Cordova, Ignacio (Ecosistemas y Recursos Agropecuarios, 2023)
Aplodinotus grunniens represent a crucial artisanal fishery in the Usumacinta River’s middle basin that generates food and a subsistence economy. This study aimed to create a model that best describes growth for A. grunniens and provides information on the growth of this poorly known pecies from the Usumacinta River. Data collection was carried out over one year through monthly sampling. A total of 447 specimens were collected from January to December 2017. Von Bertalanffy’s growth constants were calculated by separate sexes using linear fit and the non-linear Levenberg-Marquardt method. Hotelling’s T-squared test showed that growth was significantly faster in females than males. The estimated age at first maturity was two years in males and three in females. Considering the age reported for A. grunniens in other studies, the age determined in this study indicates that the population could be overexploited. Larger fish are more vulnerable to fishing pressure, mainly during their highest reproductive activity when they aggregate for spawning. More research is needed to evaluate the population status, catch per unit effort, distribution, and abundance of adults, juveniles, and larvae.